Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

y=-2x+1
4x+y=9
solve using the substitution method please show steps​


Sagot :

Answer:

x = 4

y = -7

Step-by-step explanation:

y = -2x + 1

4x + y = 9

4x + y = 9

4x + (-2x + 1) = 9

4x - 2x + 1 = 9

2x + 1 = 9

2x = 9 - 1

2x = 8

x = 8/2

x = 4

4x + y = 9

4(4) + y = 9

16 + y = 9

y = 9 - 16

y = -7